A Comparison of the 600 Yard Run-Walk and 440 Yard Run as Tests of Endurance of High School Girls - Meyer, Gloria A. (My University, 1972)
This study was an investigation to determine the relationship of the 600 yard run-walk to the 440 yard run as tests of endurance of high school girls. The study was performed with 79 freshman, sophomore, and junior high school girls during their assigned physical education classes at Parkview High School, Orfordville, Wisconsin, The Ohio State University Step Test, 600 yard run-walk, and 440 yard run were administered to each subject during a four-week period of the second semester of the 1969-70 school year. The Pearson Product-Moment Correlation Coefficient was used to determine the correlations of 0.8346 between the 600 yard run-walk and the 440 yard run, -0.5756 between the Ohio State University Step Test and 600 yard run-walk, and -0.5731 between the Ohio S t a t e University Step Test and the 440 yard run. A small sample correlated data "t" test was used to determine the significance between the means. Within the limitations of this study, it may be concluded that performance on the 600 yard run-walk and the 440 yard run are significantly related . The 600 yard run-walk and the 440 yard run test the same thing in this study, but it appears that neither test cardiovascular endurance. There is also an inverse relationship between the better performances on the runs and the Ohio State University Step Test.
Keywords: Physical fitness; Physical fitness --Testing